Application of Analysis of Variance Method in Evaluating Construction Project Cost Performance: A Case Study of the Ministry of Finance Apartment Complex in Jayapura - Erwin, Erwin (West Science Interdisciplinary Studies, 2024)
In a stage of project implementation, there are problems that can cause a project to experience cost overruns so that it can cause losses. Seeing from the problems found to get maximum results with good quality and quality of work, it is necessary to evaluate and control costs on project profits as a whole. During the construction of the Jayapura Ministry of Finance flat project, there were 5 addendums when the structural work was carried out starting from January to August. These changes have a major impact on the overall time and cost of a project and have a direct and indirect adverse impact. The method used in a control is the Variant Analysis method. Control aims to be able to find out the cost of the most dominant variant during the working period. This method will show the difference between the implementation cost and the budget. The application of this variant analysis method is only in the work of the structure of the flats of the Ministry of Finance of Jayapura from January to August. Based on the analysis using the Variance Analysis method, the most dominant cost variance occurs in the 2nd floor work item with a variance value - RP. 58,239,966.11 then in the lower structure work with a variance value - RP. 46,060,221.40 and in the 3rd floor work with a variance value - Rp. 36,434,137.98.